Aplikasi Berbagai Komposisi Bahan Baku Organik Terhadap Pertumbuhan Tanaman Cabai Rawit (Capsicum frutescens L.) - Triwuri, Nurlinda Ayu; Prasadi, Oto; Pramita, Ayu (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Fertilizer is a nutrient that is the main need for plants. One of the organic materials that is widely used as organic fertilizer is chicken manure which can have an influence on the availability of nutrients and improve the structure of soil which is very deficient in organic nutrients and can also fertilize plants. One of the dry leaves that has the potential to be used as organic fertilizer is ketapang leaves, which have a C-Organic nutrient content of 60.32%; N-Total 0.55 % ; P-Total 0.14 % ; K-Total 0.20%. In addition, the nutrient content of chicken feces is N 1%; P 0.80% ; K 0.40% and water content 55%. The wood powder content consists of chemical components such as cellulose, hemicellulose, lignin and extractive substances. This research method uses a completely randomized design, consisting of 5 treatments of various raw material compositions of chicken manure, dry ketapang leaves and wood dust. The ratio of the use of organic fertilizer and soil is 50: 50. This research aims to determine the height growth and number of leaves for cayenne pepper based on from various raw material compositions of chicken manure, ketapang leaves and wood dust. This research consisted of 5 treatments of various raw material compositions of chicken manure, dry ketapang leaves and sawdust. The ratio of organic fertilizer and soil was 50: 50. The results from observing plant height were that P1 was 6 cm high and the highest number of leaves on P2 was 7 pieces. However, the addition of organic fertilizer with various compositions does not have much effect on the growth of cayenne pepper seeds.